Limbitis Secondary to Autologous Serum Eye Drops in a Patient with Atopic Keratoconjunctivitis - Jeffrey David Welder; Pejman Bakhtiari; Ali R. Djalilian (Case Reports in Ophthalmological Medicine)
Purpose. Report a case of limbitis secondary to autologous serum eye drops in a patient with atopic keratoconjunctivitis. Design. Interventional case report. Methods. A 32-year-old African American female with atopic keratoconjunctivitis (AKC) presented with chronic dry eye and diffuse punctate epithelial erosions refractory to conservative treatment. She was initially managed with cyclosporine ophthalmic 0.05% in addition to preservative-free artificial tears and olopatadine hydrochloride 0.2% for 6 months. She was later placed on autologous serum eye drops (ASEDs) and 4 weeks into treatment developed unilateral limbitis. The limbitis resolved shortly after stopping ASEDs in that eye; however, the drops were continued in the contralateral eye, which subsequently developed limbitis within 2 weeks. ASEDs were discontinued in both eyes, and the patient has remained quiet ever since. Results. Patient with a history of AKC and no prior history of limbitis developed limbitis shortly after starting ASEDs, which resolved promptly after discontinuation of therapy with no subsequent recurrence of inflammation. Conclusion. ASEDs are widely used in the treatment of complicated or treatment refractory dry eye. The potential side effects should be kept in mind when prescribing ASEDs for any patient, especially in those with underlying immunological diseases and circulating inflammatory factors.